2019
DOI: 10.22270/jddt.v9i1.2218
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinus officinalis L.: an update review of its phytochemistry and biological activity

Abstract: Herbal medicine is one of the oldest valuable bestowals that were given to mankind. Many plants and herbs hold their prestigious position in the field of medicine. The worldwide interest in the use of medicinal plants has been growing, and its beneficial effects being rediscovered for the development of new drugs. Based on their vast ethnopharmacological applications, which inspired current research in drug discovery, natural products can provide new and important leads against various pharmacological targets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The relative quantities, presence, and/or absence of rosemary essential oils’ constituents are strongly affected by environmental conditions and agronomic management practices, as shown in literature data. According to Pintore et al [ 31 ], Angioni et al [ 10 ] demonstrated that Sardinian rosemary essential oil is an α-pinene/borneol/bornyl acetate/verbenone chemotype. Compared with our essential oils, Sardinian samples presented more content in α-pinene (~23%), borneol (~16%), bornyl-acetate (~10.4%), and camphene (~7.6%) but lower camphor content in camphor (~4.5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative quantities, presence, and/or absence of rosemary essential oils’ constituents are strongly affected by environmental conditions and agronomic management practices, as shown in literature data. According to Pintore et al [ 31 ], Angioni et al [ 10 ] demonstrated that Sardinian rosemary essential oil is an α-pinene/borneol/bornyl acetate/verbenone chemotype. Compared with our essential oils, Sardinian samples presented more content in α-pinene (~23%), borneol (~16%), bornyl-acetate (~10.4%), and camphene (~7.6%) but lower camphor content in camphor (~4.5%).…”
Section: Resultsmentioning
confidence: 99%
“…S. rosmarinus is also a rich source of essential oil [ 9 ]. Taking into account that numerous aspects, such as area of collection, time of harvest, and environmental and agronomic factors, influence the chemical composition of rosemary essential oil, several studies analysed the chemical profile of rosemary essential oil in different stages of ontogenesis in Greece [ 10 ] and Turkey [ 11 ], under the influence of different climatic factors in Tunisia [ 12 , 13 , 14 , 15 ] and Turkey [ 16 ], at different altitudes in Spain [ 17 ], and at different latitudes and longitudes in Sardinia (Italy) [ 18 ], as well as in dependence of pedological characteristics in France [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rosemary (Rosmarinus officinalis L.) belongs to the family Lamiaceae, is a medicinal plant of Mediterranean origin that has been distributed throughout different areas of the world (González-Minero et al, 2020; Kompelly et al, 2019). Rosmarinus officinalis is a woody, perennial herb with fragrant, evergreen, needle like leaves and white, pink, purple or blue flowers and found throughout India (Kompelly et al, 2019). Rosmarinus officinalis is an ancient plant considered to be medicinal in the European Pharmacopoeia (González-Minero et al, 2020; Kompelly et al, 2019).…”
Section: ) Rosemary Oil (Rosmarinus Officinalis L)mentioning
confidence: 99%
“…Rosmarinus officinalis is a woody, perennial herb with fragrant, evergreen, needle like leaves and white, pink, purple or blue flowers and found throughout India (Kompelly et al, 2019). Rosmarinus officinalis is an ancient plant considered to be medicinal in the European Pharmacopoeia (González-Minero et al, 2020; Kompelly et al, 2019). It has many medicinal properties, and its extracts have been used (mainly orally) in folk medicine.…”
Section: ) Rosemary Oil (Rosmarinus Officinalis L)mentioning
confidence: 99%
See 1 more Smart Citation